Genetic variability in Paraoxonase 1 (PON1), an HDL associated esterase: impact on risk and pharmacokinetics - Furlong, Clement (Henry Stewart Talks, 2007)
Paraoxonase (PON1), Hydrolytic reactions, Enzyme properties, Polymorphisms, Use of mouse models, PON1 levels in human populations, PON1 status as a risk factor in carotid artery disease, Designing epidemiological studies for examining PON1 genetic variability and risk
Archived at 2018/12/10